Omskepping van koöperasies in maatskappye: 'n Oorweging - W. D. Hamman; I. J. Lambrechts (South African Journal of Business Management, 1987)
– Converting co-operatives to companies: A consideration The change in the Income Tax Act in 1977 resulted in co-operatives becoming tax liable from 1 April 1977. In addition, the Co-operatives Act of 1981 resulted in additional restrictions for co-operatives. Consequently certain important advantages of cooperatives ceased. The question therefore arose whether co-operatives can still be justified as a form of organization in comparison to companies. To solve this problem several determining factors should be investigated. Aspects which should be analysed are the tax liability of each form of organization, legal restrictions of co-operatives, financing possibilities of co-operatives, the function of co-operatives as agents of control boards, and the channelling of financial assistance to organized agriculture. Co-operatives as a form of organization have definite advantages compared to companies. The most important are the declaration of deferred bonuses and the redemption of loans, which are tax deductible under certain circumstances (the latter only until 1987). There are however also disadvantages. Approval is necessary to take over companies and members do not share in the growth of co-operatives. In this article it appears that it is undesirable for co-operatives to change their form of organization in present circumstances. It is however not a categorical conclusion and the development of the determining factors should be studied continuously.
Keywords: 650